Software product assurance at the German space agency. Issue 9 (25th April 2016) - Prause, Christian R.; Bibus, Markus; Dietrich, Carsten; Jobi, Wolfgang
Abstract: The DLR Space Administration designs and implements the German space program. While project management rests with the agency, suppliers are contracted for building the space devices and their software. As opposed to many other domains, these are often unique devices with uncommon and custom‐built peripherals. Its software is specifically developed for a single mission only and controls critical functionality. A small coding error can mean the loss of a mission. For this reason, customer and supplier collaborate to improve products and processes to achieve better software at the end of a project. We discuss quality in the context of space projects, and report a cross‐sectional view from a customer's perspective on various management tools for influencing suppliers' processes and product quality: standards, single‐source tailoring and cross‐company product assurance. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : The DLR implements the German space program. While project management rests with the agency, suppliers are contracted for building the space devices and their software. Customer and supplier collaborate to improve products and processes to achieve better software at the end of a project. We discuss quality in the context of space projects, and report a cross‐sectional view from a customer's perspective on various management tools for influencing suppliers' processes and product quality.